Single-Pill Triple Fixed Dose Combination Therapy with Single Component Drug Monitoring in Treatment-Resistant Hypertension: A Pilot Study - Kreutz, Reinhold; Scholze, Jurgen; Douros, Antonios (Current Vascular Pharmacology, 2018)
Background: Single-pill fixed dose combination (FDC) therapies are widely used in the treatment of arterial hypertension. Objective: This pilot study aimed to evaluate the effects of a FDC therapy combined with therapeutic drug monitoring (TDM) on blood pressure (BP) in patients with treatment resistant hypertension. Method: The study population included patients with suspected treatment-resistant hypertension during treatment with at least 3 antihypertensive drugs. We evaluated the effect of switching all patients to a regime including a single-pill triple FDC containing olmesartan, amlodipine and hydrochlorothiazide. Adherence was evaluated by measuring serum concentrations of amlodipine in a single-blinded fashion. Results: We enrolled 13 patients (mean age 57.2±9.1 years, 8 males) with resistant hypertension (office systolic and diastolic BP 158.3±17.3 and 94.8±11.1 mmHg); mean use of antihypertensive drugs was 3.8±1.1. Medication intake of FDC was confirmed in all patients at 18 weeks. Systolic and diastolic office BP were significantly lower (-22.8 and -13.6 mmHg) after 18 weeks of treatment with triple FDC (135.5±20.1 and 81.2±6.3 mmHg, p<0.01, respectively); mean use of antihypertensive drugs was 3.8±0.9. In 9 patients with 24-h ambulatory BP monitoring (ABPM) both at baseline and after 18 weeks, 24-h mean arterial pressure decreased (-9.3 mmHg, p=0.055). Overall, 9 (69%) patients achieved BP control in office BP and 4 (31%) in 24-h ABPM. Conclusion: Our results support the use of single-pill triple FDC therapy in combination with TDM for the management of patients with suspected treatment-resistant hypertension and further testing in clinical studies.
Keywords: Antihypertensive drugs